'New and important careers': how women excelled at the BBC, 1923–1939. Issue 1 (November 2016) - Murphy, Kate
From its beginnings in 1923, the BBC employed a sizeable female workforce. The majority were in support roles as typists, secretaries and clerks but, during the 1920s and 1930s, a significant number held important posts. As a modern industry, the BBC took a largely progressive approach towards the 'career women' on its staff, many of whom were in jobs that were developed specifically for the new medium of broadcasting. Women worked as drama producers, advertising representatives and Children's Hour Organisers. They were talent spotters, press officers and documentary makers. Three women attained Director status while others held significant administrative positions. This article considers in what ways it was the modernity and novelty of broadcasting, combined with changing employment possibilities and attitudes towards women evident after the First World War, that combined to create the conditions in which they could excel.